The Combined “Double Pulley”–Simple Knot Technique for Arthroscopic Shoulder Posterior Labral Repair and Capsular Shift - Parnes, Nata (Arthrosc Tech, 2016)
Posterior shoulder instability is more prevalent than traditionally believed. Surgical repairs of posterior shoulder instability have overall good success rates. However, in elite overhead and throwing athletes, a low rate of return to the preinjury level of play after repair remains a challenge. The 2 goals of posterior shoulder stabilization surgery are secure fixation of the labrum to the glenoid and retensioning of the posterior capsulolabral complex. Recent studies have shown significant advantages of arthroscopic anatomic repair over open nonanatomic techniques. We report a combined double pulley–simple knot technique for arthroscopic fixation of posterior labral tears and capsular shift. The technique incorporates several advantages of this hybrid fixation method.